KUANTIFIKASI EMISI GAS CO2 EKUIVALEN PADA KONSTRUKSI JALAN PERKERASAN KAKU - Apsari Setiawati; Stefanus Catur Adi Prasetyo; Jati Utomo Dwi Hatmoko; Arif Hidayat (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
The construction sector is one of the major contributors to national economic development, but has great potential in environmental degradation. CO2 emissions have been used as a measure of the effect of human activities on the environment. One of the construction process that allegedly resulted in relatively large CO2e emissions is road projects. This study assessed the carbon footprint generated by the process of material production, material transport, and implementation of highway construction rigid pavement. Data is collected through direct observation of Palur Flyover Project and interviews with the project team, and project data obtained from the companies and government agencies. Road project reviewed start from STA. 0 + 350 to STA. 0 + 450 2 line of a 3 m width CO2e emissions calculations using the conversion factor from the literature. The total CO2e emissions produced during the process of rigid pavement is 92.9 tonnes of CO2e. The amount of emissions generated by the off site material production, material transport, concrete production and concrete pouring are 88 166 tonnes of CO2e (94.9%), 3,168 tonnes of CO2e (3.4%), 1,567 tons of CO2e (1.7%) respectively. Material production, cement production accounted for the largest CO2e emission (86,2%). Therefore alternative materials to cement are needed.